The relationship of survivin expression with tumour grade in gastroenteropancreatic neuroendocrine tumour (GEPNET)-USM experience - Hazmi, Hilma (2018)
Background and objective : Neuroendocrine tumours originate from the peripheral neuroendocrine cell system dispersed in all organs and is heterogenous in its presentation, localization and aggressiveness. Those arising from the gastrointestinal tract and pancreas are of interest due to its increase in incidence. The introduction of WHO 2010 classification for these tumours abates confusion on its nomenclature which depicts malignant behaviour . Survivin is an apoptosis inhibitor which are specifically expressed in tumour cells and not in normal cells. In this study we determine the clinicopathological characteristics of gastroenteropancreatic neuroendocrine tumour (GEPNET), the incidence in HUSM and the prognostic value of survivin in this tumour entity. Materials and methods: This cross-sectional study was carried out on all cases of GEPNET from 1998 to 2016 in Hospital Universiti Sains Malaysia (USM). Data on the clinicopathological characteristics and mitoses counts were noted. We performed immunohistochemical staining for survivin and Ki67 in paraffin fixed paraffin embedded blocks. Gradings according to WHO 2010 classification were done based on Ki67 proliferation index and mitoses. Results: Twenty cases of GEPNET were included in this study. There is a slight increase in GEPNET incidence in HUSM. All GEPNET presented with abdominal pain. Other vague symptoms include altered bowel habit and blood per rectum. More than half had constitutional symptoms (n=16). Majority of GEPNET arises from the gastrointestinal (n=18) and only 10% from the pancreas (n=2). 65% (n=13) demonstrated metastases. Only 40% of the cases were graded according to WHO 2010 classification since itsintroduction. 35% had serum Chromogranin A done. The commonest investigation modality is CT scan (n=16) followed by endoscopy (n=10) and ultrasound (n=6). According to the WHO 2010 classification, 60% of the GEPNET diagnosed were in Grade 3 , 15% in Grade 2 and 25% in Grade 1. There was a significant association between occurrence of metastases and gradings of GEPNET (p=0.001). There was no association between the expression of survivin and the grades in GEPNET. Conclusion: These results indicate there is an increasing trend in GEPNET incidences with variable vague presentations. There was no association found between the expression of survivin and the grades in GEPNET according to the WHO classification. Lack of database and awareness of the GEPNET and its latest classification is still a major hindrance in the diagnosis and management of the disease.